Relationship between lower limb power, flight distance from the block and swimming performance in different distances - Fernandes, Leonardo Souza; Gonçalves, Lucas de Lima; Franco, Matheus Domingues; Rodacki, Cintia de Lourdes Nahhas; Borges, Karini (Journal of Physical Education (Maringá), 2025)
The study aimed to correlate lower limb power with flight distance and crawl swimming performance over various lengths (25, 50, and 100 meters). The participants consisted of amateur athletes of both sexes, aged between 17 and 33 years. The Sargent jump test (vertical thrust) and the long jump test (horizontal thrust) were utilized to assess lower limb muscular power. Kinematic analysis of the block start was conducted using Kinovea 0.9.5. Pearson’s correlation coefficient with a significance level of p<0.05 was employed. The results indicated a moderate positive correlation between lower limb power and flight distance for the female group and a high correlation for the male group and overall (r= 0.50 to 0.83). Additionally, the results showed a moderate inverse correlation between lower limb power and swimming performance across the different distances for the male group (r= -0.40 to -0.54) and a high correlation for the general group (r= -0.69 to -0.83). These findings suggest that lower limb power training should be prioritized for sprinter swimmers and may enhance their athletic performance.